Indentured : the inside story of the rebellion against the NCAA - Nocera, Joseph; Strauss, Ben, 1986- (New York : Portfolio, 2016)
"In the four years since Joe Nocera asked those questions in a controversial New York Times column, the National Collegiate Athletic Association has come under fire. Fans have begun to realize that the athletes involved in the two biggest college sports, mens basketball and football, are little more than indentured servants. Millions of teenagers accept scholarships to chase their dreams of fame and fortune--at the price of absolute submission to the whims of an organization that puts their interests dead last. For about 5 percent of top-division players, college ends with a golden ticket to the NFL or the NBA. But what about the overwhelming majority who never turn pro? They don't earn a dime from the estimated $13 billion generated annually by college sports--an ocean of cash that enriches schools, conferences, coaches, TV networks, and apparel companies . . . everyone except those who give their blood and sweat to entertain the fans. Indentured tells the dramatic story of a loose-knit group of rebels who decided to fight the hypocrisy of the NCAA, which blathers endlessly about the purity of its 'student-athletes' while exploiting many of them: The ones who get injured and drop out because their scholarships have been revoked. The ones who will neither graduate nor go pro. The ones who live in terror of accidentally violating some obscure rule in the four-hundred-page NCAA rulebook. Joe Nocera and Ben Strauss take us into the inner circle of the NCAA's fiercest enemies. Youll meet, among others . . Sonny Vaccaro, the charismatic sports marketer who convinced Nike to sign Michael Jordan. Disgusted by how the NCAA treated athletes, Vaccaro used his intimate knowledge of its secrets to blow the whistle in a major legal case; Ed O'Bannon, the former UCLA basketball star who realized, years after leaving college, that the NCAA was profiting from a video game using his image. His lawsuit led to an unprecedented antitrust ruling; Ramogi Huma, the founder of the National College Players Association, who dared to think that college players should have the same collective bargaining rights as other Americans; Andy Schwarz, the controversial economist who looked behind the f?ade of the NCAA and saw it for what it is: a cartel that violates our core values of free enterprise. Indentured reveals how these and other renegades, working sometimes in concert and sometimes alone, are fighting for justice in the bare-knuckles world of college sports. The National Collegiate Athletic Association has come under fire. Fans have begun to realize that the athletes involved in men's basketball and football are little more than indentured servants. The ocean of cash generated by these college sports enriches schools, conferences, coaches, TV networks, and apparel companies-- everyone except those who give their blood and sweat to entertain the fans. Nocera and Strauss tell the dramatic story of a loose-knit group of rebels who decided to fight the hypocrisy of the NCAA."--Book jacket.
"Indentured tells the dramatic story of a loose-knit group of rebels who decided to fight the hypocrisy of the NCAA, which blathers endlessly about the purity of its "student-athletes" while exploiting many of them: The ones who get injured and drop out because their scholarships have been revoked. The ones who will neither graduate nor go pro. The ones who live in terror of accidentally violating some obscure rule in the four-hundred-page NCAA rulebook,"--Amazon.com.
The National Collegiate Athletic Association has come under fire. Fans have begun to realize that the athletes involved in men's basketball and football are little more than indentured servants. The ocean of cash generated by these college sports enriches schools, conferences, coaches, TV networks, and apparel companies-- everyone except those who give their blood and sweat to entertain the fans. Nocera and Strauss tell the dramatic story of a loose-knit group of rebels who decided to fight the hypocrisy of the NCAA.
"Why do they hate me so much?" -- The turncoat -- The first activist -- "How do I get one of those deals?" -- The $12 suspension -- "Somebody ought to file a lawsuit" -- The confessions of Dale Brown -- "Volandatory" practice -- Rulespalooza -- The cash king of college sports -- Ahab and the booster -- The branding of Myles Brand -- "The whole thing is ridiculous" -- The collegiate model -- A mind is a terrible thing to waste -- The deposition -- "Intent to professionalize" -- "Dude, you're on a video game!" -- The "Our way or the highway" bylaw -- "Magnifico excelentisimo" -- An excess of tutoring -- "The way you were taught to play" -- Scholarship blues -- "The whiff of the plantation" -- Actual malice -- Class is in -- Block that transfer! -- All players united -- Turning the tables on the NCAA -- Amateur hour -- The sky didn't fall -- Appendix 1. Excuses, not reasons : 13 myths about (not) paying college athletes -- Appendix 2. National Letter of Indenture : how college athletes are similar to, and in many ways worse off than, the indentured servants of colonial times.
Includes bibliographical references and index.
Keywords: National Collegiate Athletic Association; College sports -- Economic aspects -- United States; College athletes -- United States -- Economic conditions; College sports -- United States -- Management; College sports -- Moral and ethical aspects -- United States